Human rights and the olympics: from an ideological paradox to a new anti-corruption legacy - Dikaia Chatziefstathiou; J. Simon Rofe (Frontiers Media S.A., 2024)
This article aims to explore the evolution of the debates surrounding human rights in the discourse(s) of major sporting events (MSEs), particularly the Olympics. The paper will first analyse the western-centric origins of the "universality" of the Olympic philosophy and how it affected the protection and promotion of human rights, as well as addressing practical challenges or limitations faced. It will then focus on unpacking the elements of sportswashing and soft power in the multi-discursive context of sport where power, privilege, politics, and position are (re)produced. In doing so it draws upon the emergent field of Sports Diplomacy as the most appropriate explanatory framework to share in this discourse. Finally, it will explore the potential impact of anti-corruption reforms on the establishment of a meaningful human rights legacy.